Comparing Fetal and Maternal Outcomes in Pregestational and Gestational Diabetes Mellitus Patients - Zafar, Talat; Masood, Tariq; Farooq, Ammar; Batool, Subhana; Ghani, Usman (Indus Journal of Bioscience Research, 2025)
Background: Diabetes mellitus in pregnancy, encompassing both pregestational (PGDM) and gestational (GDM) forms, is a major contributor to maternal and neonatal morbidity worldwide. In low-resource settings such as Azad Jammu & Kashmir, inadequate screening and limited preconception care exacerbate these risks. Comparative data on fetomaternal outcomes between PGDM and GDM in this region remain scarce. Objective: To compare maternal and fetal outcomes among women with PGDM and GDM delivering at District Headquarters (DHQ) Hospital, Mirpur, Azad Jammu & Kashmir. Methods: This comparative cross-sectional study included 276 diabetic pregnant women (138 PGDM and 138 GDM) who delivered at DHQ Hospital between December 2023 and June 2024. Maternal outcomes assessed were preterm labour, pregnancy-induced hypertension (PIH), and postpartum haemorrhage (PPH); fetal outcomes included neonatal intensive care unit (NICU) admission, low birth weight (LBW), stillbirth, and congenital anomalies. Data were analysed using SPSS version 25.0. Chi-square tests compared proportions, with p ≤ 0.05 considered statistically significant. Stratified analyses were performed for maternal age, gestational age, mode of delivery, and residential status. Results: The mean maternal age was 27.6 ± 7.1 years, and mean gestational age at delivery was 34.4 ± 4.1 weeks. Preterm labour (26.8% vs 15.2%; p = 0.018) and PPH (10.9% vs 2.9%; p = 0.009) were significantly higher among GDM patients, whereas NICU admissions were more frequent in PGDM (47.8% vs 37.0%; p = 0.068). No significant differences were found for PIH, LBW, stillbirth, or congenital anomalies. Stratified analysis showed that the excess risks of preterm labour and PPH in GDM were pronounced in older mothers (>25 years), term pregnancies, vaginal deliveries, and urban residents, while NICU admission was significantly higher in PGDM among younger mothers (≤25 years) and preterm births. Conclusion: GDM and PGDM are both linked to serious problems throughout pregnancy and after birth. GDM was associated with enhanced risks of preterm labor and postpartum hemorrhage, whereas PGDM was connected to higher newborn morbidity. These findings underscore the significance of early screening, good glycemic management, and multidisciplinary care in all diabetic pregnancies to reduce unfavorable fetomaternal outcomes.